Bidimensional quality competition and scope economies - Paolo G. Garella; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
In markets where product quality is important, more than one characteristic is usually necessary to define product quality and the amelioration of the goods characteristics is usually costly. Then, properties of production technologies, in particular if they exhibit economies or diseconomies of scope in producing quality along several dimensions, should matter for the industry configuration at equilibrium. To date, however, the literature has neglected the issue. We analyze a duopoly model where two characteristics can be used to vertically differentiate the products. Our results are that the existence of economies of scope (resp. diseconomies of scope) leads to the emergence of a quality leader in all dimensions (resp. to a different quality leader in each characteristic).
Keywords: 330; Produktqualität; Produktdifferenzierung; Marktführer; Verbundvorteil; Theorie